2022
DOI: 10.3390/jcm11051414
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of 4D-Spatio Temporal Image Correlation (STIC) in the Comprehensive Assessment of the Fetal Heart Using FetalHQ®

Abstract: Fetal Heart Quantification (FetalHQ®) is a novel speckle tracking software that permits the study of global and regional ventricular shape and function from a 2D four-chamber-view loop. The 4D-Spatio Temporal Image Correlation (STIC) modality enables the offline analysis of optimized and perfectly aligned cardiac planes. We aimed to evaluate the feasibility and reproducibility of 4D-STIC speckle tracking echocardiography (STE) using FetalHQ® and to compare it to 2D STE. We conducted a prospective study includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(48 citation statements)
references
References 62 publications
3
45
0
Order By: Relevance
“…In this study, the intra-rater and inter-rater reliability for LV global measurements ranged from good to excellent, but RV GLS and FAC had poor reliability. Nogué et al reported poor reliability for the 24-segment SI and FS at a 60 Hz threshold, especially for the basal segments [ 47 ]. In our study, reliability was moderate to good for EDD and SI for both ventricles, but the FS had poor repeatability for the RV, especially for segment 1.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the intra-rater and inter-rater reliability for LV global measurements ranged from good to excellent, but RV GLS and FAC had poor reliability. Nogué et al reported poor reliability for the 24-segment SI and FS at a 60 Hz threshold, especially for the basal segments [ 47 ]. In our study, reliability was moderate to good for EDD and SI for both ventricles, but the FS had poor repeatability for the RV, especially for segment 1.…”
Section: Discussionmentioning
confidence: 99%
“…47 The use of four dimensional fetal echocardiography (4D-STIC) permits good resolution offline analysis and the possibility to modify the angle of insonation, the cardiac plane, and the frame for evaluation. 44,48,49…”
Section: Cardio Sticmentioning
confidence: 99%
“…The knowledge of fetal cardiac function assessment as well as fetal echocardiography itself has advanced dramatically in recent decades [1][2][3][4][5]. With its different modalities, fetal echocardiography has become indispensable for cardiac function assessment [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…With its different modalities, fetal echocardiography has become indispensable for cardiac function assessment [3,6]. With the implementation of fetal echocardiography in clinical routine, two foci arose: the detection of structural congenital cardiac defects (CHD) and subsequently the assessment of fetal cardiac morphometry and function [2,[7][8][9][10]. Fetal echocardiography is crucial for indirect evaluation of fetal ventricular size and functional parameters since the fetal heart cannot be measured directly in utero [11].…”
Section: Introductionmentioning
confidence: 99%